Interventions to prevent spontaneous preterm birth in women with singleton pregnancy who are at high risk: systematic review and network meta-analysis. (15th February 2022) - Care, Angharad; Nevitt, Sarah J; Medley, Nancy; Donegan, Sarah; Good, Laura; Hampson, Lynn; Tudur Smith, Catrin; Alfirevic, Zarko
Abstract: Objectives: To compare the efficacy of bed rest, cervical cerclage (McDonald, Shirodkar, or unspecified type of cerclage), cervical pessary, fish oils or omega fatty acids, nutritional supplements (zinc), progesterone (intramuscular, oral, or vaginal), prophylactic antibiotics, prophylactic tocolytics, combinations of interventions, placebo or no treatment (control) to prevent spontaneous preterm birth in women with a singleton pregnancy and a history of spontaneous preterm birth or short cervical length. Design: Systematic review with bayesian network meta-analysis. Data sources: The Cochrane Pregnancy and Childbirth Group's Database of Trials, the Cochrane Central Register of Controlled Trials, Medline, Embase, CINAHL, relevant journals, conference proceedings, and registries of ongoing trials. Eligibility criteria for selecting studies: Randomised controlled trials of pregnant women who are at high risk of spontaneous preterm birth because of a history of spontaneous preterm birth or short cervical length. No language or date restrictions were applied. Outcomes: Seven maternal outcomes and 11 fetal outcomes were analysed in line with published core outcomes for preterm birth research. Relative treatment effects (odds ratios and 95% credible intervals) and certainty of evidence are presented for outcomes of preterm birth <34 weeks and perinatal death. Results: Sixty one trials (17 273 pregnant women) contributed data for the analysis of at least one outcome. For preterm birth <34 weeks (40 trials, 13 310 pregnant women) and with placebo or no treatment as the comparator, vaginal progesterone was associated with fewer women with preterm birth <34 weeks (odds ratio 0.50, 95% credible interval 0.34 to 0.70, high certainty of evidence). Shirodkar cerclage showed the largest effect size (0.06, 0.00 to 0.84), but the certainty of evidence was low. 17OHPC (17α-hydroxyprogesterone caproate; 0.68, 0.43 to 1.02, moderate certainty), vaginal pessary (0.65, 0.39 to 1.08, moderate certainty), and fish oil or omega 3 (0.30, 0.06 to 1.23, moderate certainty) might also reduce preterm birth <34 weeks compared with placebo or no treatment. For the fetal outcome of perinatal death (30 trials, 12 119 pregnant women) and with placebo or no treatment as the comparator, vaginal progesterone was the only treatment that showed clear evidence of benefit for this outcome (0.66, 0.44 to 0.97, moderate certainty). 17OHPC (0.78, 0.50 to 1.21, moderate certainty), McDonald cerclage (0.59, 0.33 to 1.03, moderate certainty), and unspecified cerclage (0.77, 0.53 to 1.11, moderate certainty) might reduce perinatal death rates, but credible intervals could not exclude the possibility of harm. Only progesterone treatments are associated with reduction in neonatal respiratory distress syndrome, neonatal sepsis, necrotising enterocolitis, and admission to neonatal intensive care unit compared with controls. Conclusion: Vaginal progesterone should be considered the preventative treatment of choice for women with singleton pregnancy identified to be at risk of spontaneous preterm birth because of a history of spontaneous preterm birth or short cervical length. Future randomised controlled trials should use vaginal progesterone as a comparator to identify better treatments or combination treatments. Systematic review registration: PROSPERO CRD42020169006